Analysis of the Impact of Mobile Banking Technology, Fintech, and Digital Transaction Security on Customer Loyalty at BUMN Banks in Indonesia - Judijanto, Loso; Ariyanti, Rini; Suryani, Sri (West Science Social and Humanities Studies, 2024)
This study investigates the impact of mobile banking technology, fintech innovations, and digital transaction security on customer loyalty at state-owned banks in Indonesia. Utilizing a quantitative approach, data were collected from 300 respondents through a structured questionnaire with a Likert scale ranging from 1 (Strongly Disagree) to 5 (Strongly Agree). The data were analyzed using SPSS version 25, employing descriptive statistics, reliability analysis, exploratory factor analysis, correlation analysis, and multiple regression analysis. The results revealed that all three independent variables—mobile banking technology, fintech innovations, and digital transaction security—positively and significantly influence customer loyalty. Mobile banking technology had a correlation coefficient of 0.62, fintech innovations 0.57, and digital transaction security 0.68 with customer loyalty. The regression analysis showed that these factors collectively explained 38% of the variance in customer loyalty, with digital transaction security having the strongest impact. The findings underscore the importance of enhancing technological capabilities and security measures to foster customer loyalty in state-owned banks. The study provides valuable insights for banking institutions seeking to improve customer satisfaction and retention through advanced technological solutions and robust security protocols.